Role of minor autohemotherapy in the prevention of COVID-19 in institutionalized elderly. Case report (Ozone Therapy Global Journal, 2021)
The disease caused by SARS-CoV-2 known as COVID19 was declared a pandemic in March 2020 by the World Health Organization (WHO). The institutionalized elderly population has been the most affected by high morbidity and mortality associated with risk factors and poor prognosis such as age (over 65 years), high blood pressure, diabetes Mellitus, obesity, among others. Ozone therapy has proven to be a great ally in the complementary treatment of patients with COVID19.Objective: To determine the efficiency and safety of minor autohemotherapy in the preventive treatment of COVID-19 in institutionalized risk patients.Case report: 35 patients from a nursing home, 21 residents and 14 workers aged between 26 and 98 years were treated with minor autohemotherapy. There was only one case of a 90-year-old asymptomatic resident with a positive serological test and no contagion to the rest of the cohabiting patients. During the treatment no side effects were observed. Secondarily, none of the patients has had respiratory infections associated or not with COVID 19 and the glycemic profiles of diabetics have improved.Conclusion: Minor autohemotherapy was found to be safe and effective as a preventive treatment for COVID19 in treated patients. However, more clinical studies are needed to demonstrate the possible benefits of ozone therapy.